The efficiency and distributive effects of local taxes: Evidence from Italian municipalities - Enrico Rubolino (University of Essex, Institute for Social and Economic Research (ISER), 2019)
This paper analyzes the effect of local income taxation on taxable income, inequality and internal migration in Italy using two tax reforms and several administrative data sources. These reforms, introduced in 2007 and 2011, granted municipalities the authority to switch from a flat to a progressive local income tax. I obtain two main results. First, the progressive tax reduced taxable income by 5 percent and the income share held by the top percentile of the municipal income distribution by 6 percent. Second, I find compelling evidence of a positive effect of net-of-tax rate differentials across provinces on changing fiscal residence.
Keywords: D31; H21; H24; H30; H71; 330; Local income tax; Tax progressivity; Taxable income elasticity; Income inequality; Tax-induced migration